Mitochondrial Function in Hereditary Spastic Paraplegia: Deficits in SPG7 but Not SPAST Patient-Derived Stem Cells - Wali, Gautam; Kumar, Kishore Raj; Liyanage, Erandhi; Davis, Ryan L.; Mackay-Sim, Alan; Sue, Carolyn M. (Frontiers in Neuroscience, 2020)
Mutations in SPG7 and SPAST are common causes of hereditary spastic paraplegia (HSP). While some SPG7 mutations cause paraplegin-deficiency, other SPG7 mutations cause increased paraplegin expression. Mitochondrial function has been studied in models that are paraplegin-deficient (human, mouse and Drosophila models with large exonic deletions, null mutations or knockout models) but not in models of mutations that express paraplegin. Here, we evaluated mitochondrial function in cells derived from patients with a variety of SPG7 mutations that express paraplegin and compared them to cells derived from healthy controls and HSP patients with SPAST mutations, as a disease-control. We quantified paraplegin expression and an extensive range of mitochondrial morphology measures (fragmentation, interconnectivity, mass), mitochondrial function measures (membrane potential, oxidative phosphorylation, oxidative stress), and cell proliferation. Compared to control cells, SPG7 patient cells had increased paraplegin expression, fragmented mitochondria with low interconnectivity, reduced mitochondrial mass, decreased mitochondrial membrane potential, reduced oxidative phosphorylation, reduced ATP content, increased mitochondrial oxidative stress and reduced cellular proliferation. Mitochondrial dysfunction was specific to SPG7 patient cells and not present in SPAST patient cells, which displayed mitochondrial functions similar to control cells. The mitochondrial dysfunction observed here in SPG7 patient cells that express paraplegin was similar to the dysfunction reported in cell models without paraplegin expression. The p.A510V mutation was common to all patients and was the likely species associated with increased expression, albeit seemingly non-functional. The lack of a mitochondrial phenotype in SPAST patient cells indicates genotype-specific mechanisms of disease in these HSP patients.